Stability of commercially available lactobacillus products - D S Pollmann; C A Bandyk (Kansas Agricultural Experiment Station Research Reports, 1982)
A study was conducted to determine the viability of three commercially available lactobacillus products in nonmedicated and medicated (lincomycin at 100 grams per ton) swine feed in several different environments over a 3-month period. Each product was stored in five environments: refrigeration (40°F), room temperature (70°F) in sealed container, room temperature in unsealed container, swine nursery (90°F) in a sealed container, and swine nursery in an unsealed container. Feed samples were counted for lactobacillus at weeks 0, 1, 3, 5, 7, and 12 with four replications. The three commercial products differed in stability while maintained in the various environmental conditions. Refrigerated storage prolonged (P<.05) stability of all products. Stability of products stored at room temperature was greater than those stored in the nursery (P<.05). Medication had a slight adverse affect on the product stability. There were no differences between samples stored in sealed or open containers. These results demonstrate that the stability of viable lactobacillus products can be influenced by storage environment, length of storage, and type of medication in the feed.; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422; Swine; Lactobacillus products